Kelayakan Usaha Ternak Kambing Menurut Sistem Pemeliharaan, Bangsa, dan Elevasi di Yogyakarta - Tri Anggraeni Kusumastuti (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2012)
The objective of this study was to analyze the feasibility business for goat based on keeping system, keept, the livestock breed and elevation. The study was carried out in four districts of Yogyakarta. Purposive random techniques were used. The samples were selected based on the village group system, breeds (Kacang, Bligon and Etawa Crossbreed Goat and elevation (low, medium and high). The socio-economic were the Break Even Point, B/C ratio, and Net Present Value (NPV) of the farmers. The results showed that Etawa Crossbreed Goat have a highest income to increase the productivity of goats. Moreover, the goat breeding business was profitable when there were minimally 2-3 doe on the assumption that the livestock breeding was intensively managed. In general, the B/C ratio value was bigger than 1 and the NPV was positive, indicated that the goat was feasible because it could provide the breeders with the profit that surpassed the social opportunity cost, which was the used capital production factor. It is recommended that Kacang goats may be developed due to the pure breed and good export opportunity.Key words : feasibility study, the keeping system, livestock breed, elevation